Impact of loan sales towards asset risk of Malayan Banking Berhad / Sahidah Zakariah - Zakariah, Sahidah (2008)
Selling loans is hardly new and the key objective is to remove these loans from the balance sheet ) that banks do not have to continue making provisions for them. In fact, during the dark days when the the region stagnated under the shadow of Asian financial crisis, housing loan worth some RM8 billion had been acquired by CAGAMAS to help support ailing banking system. Through sales, benefits are achieved for banking institutions that act as loan originators. Many have shown the empirical benefits of loan sales via securitization, and the constructive effects it has on variability of banking capital. This paper empirically analyzes the impact of loan sales (specifically in housing loan sold to agamas) toward asset risk on Malayan Banking Berhad. Despite the fact that, the main fictive is to determined the relationship between loan sales and asset risk and also found out whether loan sales activities give an impact toward asset risk faced by Malayan Banking Berhad. The time frame of the research conducted is within ten years. Where, the data which have been used in this research is between year 1998 up to year 2007.The hypothesis was being tested using Pearson Correlation Coefficient and also Linear egression. The result gathered after hypothesis testing shows that loan sales have significant relationship with asset risk (where asset risk have been represented by ratio of loan sold to total sets, ratio of deposit to loan over 5 year maturity, ratio of loan loss reserves to total loan, and ratio of landed property loan to total asset).